2014
DOI: 10.1109/tim.2014.2318371
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of PEM Fuel Cell Drying and Flooding Based on Power Converter Ripple

Abstract: This paper discusses the possibility to use the current ripple introduced by switch mode power converters for low-cost monitoring of polymer electrolyte membrane (PEM) fuel cell (FC) state-of-health, suitable for commercial applications that cannot afford dedicated instrumentation. In more details, an estimate of the ohmic resistance, which is a good indicator of the membrane water content, can be obtained from the high-frequency ripple response by data processing in the frequency domain, while lower frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Such systems including PEM fuel cells are vulnerable to system failure or mechanical faults that can lead to catastrophic consequences. Among different kinds of fuel cells, PEM fuel cells are suitable for both stationary and automobile applications due to the ongoing development of PEM technology [5].…”
Section: Robust Model-based Fault Diagnosis For Pem Fuelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such systems including PEM fuel cells are vulnerable to system failure or mechanical faults that can lead to catastrophic consequences. Among different kinds of fuel cells, PEM fuel cells are suitable for both stationary and automobile applications due to the ongoing development of PEM technology [5].…”
Section: Robust Model-based Fault Diagnosis For Pem Fuelmentioning
confidence: 99%
“…Zhang et al [24] proposed a state space model based fault detection method for a hybrid system which consists of three DC power sources, fuel cells, photovoltaic and batteries. More recently, Dotelli et al [5] proposed a diagnostic approach for detecting PEM fuel cell drying and flooding by analyzing the current ripple generated from the switching power converters. It should be noted that the model used in the above works are obtained from Jacobian linearization approach around pre-defined operating points of the system.…”
Section: Nomenclaturementioning
confidence: 99%
“…To avoid the effects of numerical errors that may arise due to the 16-bit numerical format employed in the FPGA, the average values of the voltage and current ramps are subtracted from the next acquired ramps, so that in steady-state conditions, the dc components of the processed signals are much smaller than the peak-to-peak amplitudes. The estimated increasing and decreasing ramp slope values in each switching period, together with the number of samples on which the estimation was based, are then passed to a 400-MHz-clock real-time processor that is also included in the Compact-RIO, where the weighted averages (11) and (12) are calculated and the best estimate of the ohmic resistance in the selected time window (1000 switching periods) is finally evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…With this aim, the use of switch-mode power converter ripple for high-frequency impedance measurements was suggested in a few papers in the literature as a cost-effective approach to estimate the FC ohmic resistance [10], [11]. Previous works of the authors showed how a model-based elaboration of the FC response to the converter ripple in the frequency domain can provide accurate ohmic resistance estimates suitable for diagnostic purposes [12] and the proposed approach was successfully tested with a specifically designed dc/dc converter [13]. References [14] and [15] also showed how ad hoc injection of lower-frequency components in the ripple waveform allows one to measure the lower-frequency impedance as well as the ohmic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic simulation model of PEM fuel cell can be used for analysis the grid connected and standalone applications. The PEM fuel cell system can be easily integrated to the existing wind generations system [6]- [8].…”
Section: Introductionmentioning
confidence: 99%